Qatar Charity's role in providing relief to Syrian refugees during the winter of 2024 in Jordan - Alsharo, Sahar Yousef (Journal of Humanities & Social Sciences, 2024)
The civil war in Syria has greatly affected individuals and caused them to lose their homes, forcing them to flee and seek refuge in different countries to protect themselves and their families. Jordan was one of the countries that hosted a large number of Syrian refugees, reaching approximately 1.2 million refugees, which is a worrying number. Jordan sought to meet the needs of refugees and basic living requirements, which led to the depletion of Jordanian resources and a major impact on Jordanian society in general. This research paper explains the role of international organizations in helping Syrian refugees in Jordan. It also studies the projects and initiatives undertaken by Qatar Charity that aim to provide aid and assistance to victims of wars and their impact on the lives of refugees. The most important goal is to shed light on Qatar Charity as the most important charitable organization and its essential role in providing relief to refugees.
Keywords: The role of Qatar Charity; Syrian refugees; the impact of the war in Syria on individuals; the reasons for the displacement of Syrians